Phoradendron longicaule (Viscaceae): a new species from Michoacán, Mexico - Kuijt, Job; Steinmann, Victor W. (Phytotaxa, 2016)
Phoradendron longicaule (Viscaceae), a new, nearly leafless species of mistletoe from the Infiernillo-Zicuirán Biosphere Reserve of southern Michoacán, Mexico, is described and illustrated. It occurs in a tropical deciduous forest at elevations of 400 to 500 m, and all known hosts belong to Fabaceae. The long, straight, pendulous stems and elongated vegetative internodes are distinctive features. It is most similar to P. nudum but differs by having 3 or 4 pistillate flowers per fertile bract, expanded albeit highly reduced leaves, and longer vegetative internodes. It is also similar to P. teretifolium from which it differs by having a pendulous habit, longer vegetative internodes, 3 or 4 pistillate flowers per fertile bract, and fruits on short internodes.